2013
DOI: 10.1542/peds.2012-2112
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth and Newborn Mortality in India After Helping Babies Breathe Training

Abstract: HBB training reduced SB without increasing NMR, indicating that resuscitated infants survived the neonatal period. Monitoring and community-based assessment are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
156
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(176 citation statements)
references
References 23 publications
15
156
5
Order By: Relevance
“…A large study in India demonstrated that a single course provided 6–8 months after initial training can also increase trainees’ simulation scores back to the high level initially attained [11], but did not evaluate retention past the immediate post-refresher period. To date, our results appear to be unique in demonstrating that performance following an HBB refresher course is more sustained than after the initial course alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large study in India demonstrated that a single course provided 6–8 months after initial training can also increase trainees’ simulation scores back to the high level initially attained [11], but did not evaluate retention past the immediate post-refresher period. To date, our results appear to be unique in demonstrating that performance following an HBB refresher course is more sustained than after the initial course alone.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the largest, most methodologically sound studies evaluating the HBB’s impact demonstrate a decrease in either newborn mortality rate (NMR) or fresh stillbirth rate (FSR) from before to after training mostly at large hospitals where data collection occurred before HBB was provided [1115]. As discussed above, since the relative burden of newborn mortality is likely more significant in rural regions not regularly attended by physicians, birth attendants working in these areas are in greater need of resuscitation skills and therefore are a more ideal target population for HBB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on evaluating differences in steps of neonatal resuscitation between LBW and NBW infants; therefore it is difficult to compare with previous observational studies of HBB interventions. However, HBB training in Nepal and India resulted in an increased rate of ventilation whereas the same intervention in Tanzania demonstrated a lower rate of ventilation after training [68]. …”
Section: Discussionmentioning
confidence: 99%
“…The Helping Babies Breathe (HBB) protocol was developed to respond to the need for increased coverage of clinical skills regarding neonatal resuscitation in low-income settings [5]. Studies on outcomes in low-income settings after training in HBB have demonstrated a reduction in intrapartum stillbirths along with reduced or unchanged early neonatal mortality [68]. The results imply that newborns who would have previously been classified as stillbirths were successfully resuscitated post-training.…”
Section: Introductionmentioning
confidence: 99%